Formation of individual stripes in a mixed-dimensional cold-atom Fermi–Hubbard system - Dominik Bourgund; Thomas Chalopin; Petar Bojović; Henning Schlömer; Si Wang; Titus Franz; Sarah Hirthe; Annabelle Bohrdt; Fabian Grusdt; Immanuel Bloch; Timon A. Hilker (Nature, 2025)
AbstractThe relation between d-wave superconductivity and stripes is fundamental to the understanding of ordered phases in high-temperature cuprate superconductors1–6. These phases can be strongly influenced by anisotropic couplings, leading to higher critical temperatures, as emphasized by the recent discovery of superconductivity in nickelates7–10. Quantum simulators with ultracold atoms provide a versatile platform to engineer such couplings and to observe emergent structures in real space with single-particle resolution. Here we show, to our knowledge, the first signatures of individual stripes in a cold-atom Fermi–Hubbard quantum simulator using mixed-dimensional (mixD) settings. Increasing the energy scale of hole–hole attraction to the spin exchange energy, we access the interesting crossover temperature regime in which stripes begin to form11. We observe extended, attractive correlations between hole dopants and find an increased probability of forming larger structures akin to individual stripes. In the spin sector, we study correlation functions up to the third order and find results consistent with stripe formation. These observations are interpreted as a precursor to the stripe phase, which is characterized by interleaved charge and spin density wave ordering with fluctuating lines of dopants separating domains of opposite antiferromagnetic order12–14.